2009
DOI: 10.1177/1933719109336678
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Hypoxia Increases Endothelial Nitric Oxide Synthase Expression in the Ovine Fetal Adrenal

Abstract: This study was designed to test the hypothesis that fetal adrenal nitric oxide synthase (NOS) is elevated in response to long term hypoxia (LTH). Pregnant ewes were maintained at high altitude (3,820 m) for approximately the last 100 days of gestation. Between days 138-141 of gestation, adrenal glands were collected from LTH fetuses and age-matched normoxic controls. qRT-PCR and Western analysis were used to quantify NOS expression and NOS distribution was examined by immunohistochemistry and double-staining i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
34
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(40 citation statements)
references
References 50 publications
6
34
0
Order By: Relevance
“…Nitric oxide, similarly to prostaglandins, can modulate the release of stress hormones such as CRH, vasopressin, ACTH and corticosterone (Bugajski et al 2004, Rettori et al 2009). NOS activity is increased during stress and infection (Gadek-Michalska et al 2005, Monau et al 2009). Nitric oxide can regulate cortical and medullary adrenal gland functions such as the secretion of aldosterone (Sainz et al 2004) and corticosterone (Cymeryng et al 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Nitric oxide, similarly to prostaglandins, can modulate the release of stress hormones such as CRH, vasopressin, ACTH and corticosterone (Bugajski et al 2004, Rettori et al 2009). NOS activity is increased during stress and infection (Gadek-Michalska et al 2005, Monau et al 2009). Nitric oxide can regulate cortical and medullary adrenal gland functions such as the secretion of aldosterone (Sainz et al 2004) and corticosterone (Cymeryng et al 1998).…”
Section: Discussionmentioning
confidence: 99%
“…In that study, however, staining for nNOS was not apparent. We suggested that the differences in nNOS expression between adult and fetus were due to developmental changes (Monau et al 2009). We also demonstrated very low expression levels of iNOS mRNA, but iNOS protein was undetectable with either western analysis or immunohistochemistry.…”
Section: Cellular Localization Of Nos In Endocrine Tissuementioning
confidence: 98%
“…eNOS clearly colocalized with CYP17, a key enzyme involved in cortisol synthesis that is expressed in cells of the zona fasciculata (Monau et al 2009). Together, these data further reinforce the concept that adrenal cortical cells express eNOS and that NO produced locally may play a role in local regulation of cortisol synthesis.…”
Section: Cellular Localization Of Nos In Endocrine Tissuementioning
confidence: 99%
See 2 more Smart Citations